COVID, CITIES and CLIMATE: Historical and Potential Transitions for the New Economy - Newman, Peter (MDPI, 2020)
The 2020 collapse of the global economy due to the Covid-19 pandemic has enabled us to think about long term trends and what the future could hold for our cities and regions, especially due to the climate agenda. The paper sets out the historical precedents for economic transitions after collapses that unleash new technologically based innovation waves. These are shown to be associated with different energy and infrastructure priorities and their transport and resulting urban forms. The new technologies in the past were emerging but mainstreamed as the new economy was built on new investments. The paper suggests that the new economy, for the next 30 years, is likely to be driven by the Paris Agreement and Sustainable Development Goals (SDGs) agendas (summarised as zero carbon–zero poverty) and will have a strong base in a cluster of innovative technologies: renewable energy, electromobility, smart cities, hydrogen-based industry, circular economy technologies, and biophilic urbanism. The first three are well underway, and the other three will need interventions if not cultural changes and may miss being mainstreamed in this recovery but could still play a minor role in the new economy. The resulting urban transformations are likely to build on Covid-19 through “global localism” and could lead to five new features: (1) relocalised centres with distributed infrastructure, (2) tailored innovations in each urban fabric, (3) less car dependence, (4) symbiotic partnerships for funding, and (5) rewritten manuals for urban professionals. This period needs human creativity to play a role in revitalising the human dimension of cities. The next wave following this may be more about regenerative development.